Changes in the mast cell distribution in the canine ovary and uterus throughout the oestrous cycle. Issue 4 (3rd February 2020) - Hamouzova, Pavla; Cizek, Petr; Bartoskova, Alena; Vitasek, Roman; Tichy, Frantisek
Abstract: This is the first study describing the relation between the phase of the oestrous cycle and the number of mast cells (MCs) in the canine ovaries and uterine horns. The total number of MCs was counted in cortex ovarii, medulla ovarii, endometrium and myometrium . The number of MCs was compared in all of these areas among the bitches in the early follicular phase, luteal phase and anoestrus. MCs were the most numerous in the early follicular phase and in the luteal phase; however, they were significantly less numerous during anoestrus. Based on the results, it was concluded that the number of MCs in ovaries and uterine horns fluctuates during the oestrous cycle. The results of this study may contribute to clarifying the role of MCs in the reproductive organs of bitches.